Dehidrasi Bioetanol Dari Nira Tebu (Saccharum officinarum) Dengan Proses Adsorpsi Menggunakan Bentonite Clay - Shafwan Amrullah; Nurkholis; Wahyuda Pratama (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2021)
The increase in population will automatically increase the use of motorized fuel, especially motorbikes and cars. That way, of course the need for fuels such as petrol, diesel, and the like will continue to increase, so there is a need for alternative renewable fuels such as bioethanol which is a renewable fuel that can substitute for these needs. Bioethanol itself is known to have a knock rate value equal to the gasoline and diesel phases when the purity reaches 99.5%. In this study, the characterization process of bioethanol products made from sugarcane juice was carried out using bentonite clay purifiers and looked at the characteristics of pH, brix, and bioethanol content. This research was conducted experimentally, using a completely randomized design (CRD) with 3 treatments, namely variations in the weight of bentonite clay 40 grams, 50 grams, and 60 grams with 3 replications. The results showed that there was an effect of adding variations in the weight of bentonite clay on the bioethanol content of sugarcane juice and there was an effect on the pH value, but there was no effect on the sugar content (brix). The best treatment in this study was bioetano from sugarcane juice with the addition of a weight of 60 grams, with alcohol content production of 9.33%, a pH of 5.13, and 6.33% brix.